1989
DOI: 10.1051/apido:19890206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brood production and population size on honey production of honeybee colonies in Alberta, Canada

Abstract: Summary — Honey production of 23 honey bee (Apis mellifera) colonies was recorded for 2 consecutive years. Brood areas and colony populations were measured during the honeyflow.One-, 2-, and 3-yr-old queens were used. The mean honey production was 120.2 kg per colony, varying from 60.9 to 210.8 kg. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
2
4

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 4 publications
5
18
2
4
Order By: Relevance
“…They are also within those reported by Szabo (1982) for different apiaries and months in Canada (r = 0.13 to 0.89), and within those presented by Szabo and Lefkovitch (1989) for two dates during two years in Canada (r = 0.15 to 0.65).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They are also within those reported by Szabo (1982) for different apiaries and months in Canada (r = 0.13 to 0.89), and within those presented by Szabo and Lefkovitch (1989) for two dates during two years in Canada (r = 0.15 to 0.65).…”
Section: Discussionsupporting
confidence: 91%
“…Szabo and Lefkovitch (1989) reported that the correlation between the worker population and honey production was; r = 0.62, and according to Genc and Aksoy (1993), it was r = 0.66.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…, Szabo (1982) und Bienefeld (1988) (Pirchner et al, 1960;Soller und BarCohen, 1967;Bar-Cohen et al, 1978;Szabo, 1982;Woyke, 1984aWoyke, , 1984bSzabo und Lefkovitch, 1989) (1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989). Traits recorded were honey yield (HL), the subjectively judged behavioral traits quietness (RU), a combination of aggressiveness and calmness, and swarming (SN) (score ranging from 1 = worst to 4 = best), and, though not available with all observations, the number of combs covered with bees both after hibernation (VA) and at the beginning of main honey flow (BT).…”
mentioning
confidence: 99%
“…Several other variables are correlated with seasonal colony weight gain or honey production. These include colony population (Farrar, 1937;Szabo, 1982;Szabo and Lefkovitch, 1989), 24-h pollen collection (Szabo, 1982), area of sealed brood (Soller and Bar-Cohen, 1967;Szabo, 1982;Szabo and Lefkovitch, 1989), weight of bees in colony (Szabo, 1982), daily flight activity (Szabo, 1980), queen weight (Nelson and Gary, 1983), and several morphological characteristics (Milne, 1980(Milne, , 1985Milne and Pries, 1984;Szabo and Lefkovitch, 1988). Szabo (1982) (Laidlaw, 1987a, b) or isolated mating yards (Ruttner, 1988;Waller et al, 1989).…”
Section: Introductionmentioning
confidence: 99%